Green Communications and Networking First International Conference, GreeNets 2011, Colmar, France, October 5-7, 2011, Revised Selected Papers - Rodrigues, Joel J. P. C.; Zhou, Liang; Chen, Min.; Kailas, Aravind; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the First International Joint Conference on Green Communication and Networking (GreeNets 2011), held in Colmar, France, on October 5-7, 2011. The 16 revised full papers presented were carefully selected and reviewed from numerous submissions and explain the scope and challenges of designing, building, and deploying GreeNets. In this regard, the conference aims to establish a forum to bring together research professionals from diverse fields including green mobile networks, system architectures, networking & communication protocols, applications, test-bed and prototype, traffic balance and energy-efficient cooperation transmission, system and application issues related to GreenNets.
A New Energy Prediction Approach for Intrusion Detection in Cluster-Based Wireless Sensor Networks -- A Smart Appliance Management System with Current Clustering Algorithm in Home Network -- A Flexible Boundary Sensing Model for Group Target Tracking in Wireless Sensor Networks -- Green Femtocell Networking with IEEE 802.16m Low Duty Operation Mode -- An Android Multimedia Framework Based on G streamer -- Bandwidth Aware Application Partitioning for Computation Offloading on Mobile Devices -- A Content-Centric Architecture for Green Networking in IEEE 802.11 MANETs -- TOA Ranging Using Real Time Application Interface (RTAI) in IEEE 802.11 Networks -- Power Reduction in WDM Mesh Networks Using Grooming Strategies -- Power Consumption Analysis of Data Center -- Gradient Optimisation for Network Power Consumption -- On Multipath Transmission Scheduling in Cognitive Radio Mesh Networks -- On the Use of Cooperation as an Energy-Saving Incentive in Ad Hoc Wireless Networks -- Cooperation Policy Selection for Energy-Constrained Ad Hoc Networks Using Correlated Equilibrium -- Energy- and Spectral-Efficient Wireless Cellular Networks -- Energy Packet Networks: ICT Based Energy Allocation and Storage.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Engineering economy; Computer Science; Computer Communication Networks; Computers and Society; Energy Economics; Computer Systems Organization and Communication Networks; Computer Applications